Role of the Ubiquitin System in Chronic Pain - Cheng, Jiurong; Deng, Yingdong; Zhou, Jun (Frontiers in Molecular Neuroscience, 2021)
As a significant public health issue, chronic pain, mainly neuropathic pain (NP) and inflammatory pain, has a severe impact. The underlying mechanisms of chronic pain are enigmatic at present. The roles of ubiquitin have been demonstrated in various physiological and pathological conditions and underscore its potential as therapeutic targets. The dysfunction of the component of the ubiquitin system that occurs during chronic pain is rapidly being discovered. These results provide insight into potential molecular mechanisms of chronic pain. Chronic pain is regulated by ubiquitination, SUMOylation, ubiquitin ligase, and deubiquitinating enzyme (DUB), etc. Insight into the mechanism of the ubiquitin system regulating chronic pain might contribute to relevant therapeutic targets and the development of novel analgesics.